Beyond Slavery: Overcoming Its Religious and Sexual Legacies - Teel, Karen (A journal of church and state, 2012)
Beyond Slavery grew out of the multi-year Feminist Sexual Ethics Project, including a major conference at Brandeis University in 2006. Attending the conference, I found the presentations tantalizingly short and have eagerly anticipated the volume. This groundbreaking, polished collection surpasses expectations. The collaborators provide rich historical, sociological, and religious context for persistent and pernicious inequities in contemporary human relationships., Bernadette Brooten's expertly crafted introductory essay, one of the best I have seen for an edited volume, weaves the book's wide-ranging topics into a status report on the sexual legacy of slavery across the Abrahamic faiths.